PRKN regulates inner mitochondrial membrane PHB2 during mitophagy - Shan Sun; Hongfeng Wang; Qilian Ma; Ningning Li; Mian Cao; Kin Yip Tam; Zheng Ying (Autophagy Reports, 2023)
PINK1 (PTEN induced kinase 1) and PRKN-mediated mitophagy is an important mitochondrial quality control pathway which selectively degrades damaged mitochondria and is tightly associated with neurodegenerative diseases, including Parkinson disease and amyotrophic lateral sclerosis. The current model of PINK1-PRKN-mediated mitophagy is that PRKN ubiquitinates multiple outer mitochondrial membrane (OMM) proteins, and then the ubiquitin chains on the OMM interact with autophagy receptors which bind Atg8-family protein labeled phagophores. However, little work has been focused on the PRKN-mediated ubiquitination of inner mitochondrial membrane (IMM) proteins during mitophagy. Our recent work revealed that PRKN binds and ubiquitinates PHB2 (prohibitin 2), an essential IMM protein which was previously recognized as a mitophagy receptor, after the OMM is ruptured by proteasomal degradation. Using biochemical and microscopy approaches, we found that mutations of PRKN-targeted ubiquitination sites on PHB2 decrease the recognition of damaged mitochondria by the phagophore and the clearance of damaged mitochondria. In conclusion, our findings revealed a critical role for PRKN-PHB2 interaction in mitochondrial quality control by regulating IMM-associated recognition of mitochondria by the autophagy machinery.